Rekonstruksi Politik Hukum Pidana Nasional (Telaah Kritis Larangan Analogi dalam Hukum Pidana) - Tongat Tongat (The Constitutional Court of the Republic of Indonesia, 2015)
A paradigm shift in the state of life—especially post the Constitution of the Republic of Indonesia 1945 amendments—have not been fully understood properly. Up to now—included in the lawless life—is still a gap between the paradigm and its implementation . This paradigmatic gap visible example of the lack of a comprehensive implementation of the basic principles of the Constitution of the Republic of Indonesia 1945 in a national criminal law reform ( draft Code of Criminal Law ) . The draft Code of Criminal Law as one form of national criminal law reform is seen has not fully represent constitution demands. Prohibiting the use of analogy in criminal law is still seen at odds with the provisions of Article 1 ( 3 ) of the Constitution of the Republic of Indonesia 1945. The gap is not only paradigmatic potential to cause difficulties in its application, but also potentially the cancellation clause in the legislation concerned.